Establishing optimal cutoff values for high-sensitivity cardiac troponin algorithms in risk stratification of acute myocardial infarction. - Liu, Li; Lewandrowski, Kent (Critical Reviews in Clinical Laboratory Sciences, 2024)
Acute myocardial infarction (AMI) is a leading cause of mortality globally, highlighting the need for timely and accurate diagnostic strategies. Cardiac troponin has been the biomarker of choice for detecting myocardial injury. A dynamic change in concentrations supports the diagnosis of AMI in the setting of evidence of acute myocardial ischemia. The new generation of high-sensitivity cardiac troponin (hs-cTn) assays has significantly improved analytical sensitivity but at the expense of decreased clinical specificity. As a result, sophisticated algorithms are required to differentiate AMI from non-AMI patients. Establishing optimal hs-cTn cutoffs for these algorithms to rule out and rule in AMI has been the subject of intensive investigations. These efforts have evolved from examining the utility of the hs-cTn 99th percentile upper reference limit, comparing the percentage versus absolute delta thresholds, and evaluating the performance of an early European Society of Cardiology-recommended 3 h algorithm, to the development of accelerated 1 h and 2 h algorithms that combine the admission hs-cTn concentrations and absolute delta cutoffs to rule out and rule in AMI. Specific cutoffs for individual confounding factors such as sex, age, and renal insufficiency have also been investigated. At the same time, concerns such as whether the small delta thresholds exceed the analytical and biological variations of hs-cTn assays and whether the algorithms developed in European study populations fit all other patient cohorts have been raised. In addition, the accelerated algorithms leave a substantial number of patients in a non-diagnostic observation zone. How to properly diagnose patients falling in this zone and those presenting with elevated baseline hs-cTn concentrations due to the presence of confounding factors or comorbidities remain open questions. Here we discuss the developments described above, focusing on criteria and underlying considerations for establishing optimal cutoffs. In-depth analyses are provided on the influence of biological variation, analytical imprecision, local AMI rate, and the timing of presentation on the performance metrics of the accelerated hs-cTn algorithms. Developing diagnostic strategies for patients who remain in the observation zone and those presenting with confounding factors are also reviewed.